2005
DOI: 10.1007/s11172-005-0258-8
|View full text |Cite
|
Sign up to set email alerts
|

Borohydride reduction of acetophenone and esters of dehydrocarboxylic acids in the presence of chiral cobalt(II) diamine complexes

Abstract: The catalytic reduction of acetophenone, methyl α acetamidocinnamate, and dimethyl itaconate with alcohol modified sodium borohydride was studied in the presence of complexes CoCl 2 •L 2 (L 2 are chiral C 2 symmetric diamines: (4S,5S) 2,2 dimethyl 4,5 bis(amino methyl) 1,3 dioxolane, (4S,5S) 2,2 dimethyl 4,5 bis(methylaminomethyl) 1,3 dioxolane, (4S,5S) 2,2 dimethyl 4,5 bis(dimethylaminomethyl) 1,3 dioxolane, and (4S,5S) 2,2 di methyl 4,5 bis(diphenylaminomethyl) 1,3 dioxolane). The maximum enantiomeric excess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Thus, base metal catalysts that expand the range of substrates that can be hydrogenated with synthetically useful enantioselectivity would be valuable. While selected examples of asymmetric alkene hydrogenation are known, H 2 is often not the stoichiometric reductant and the yields and selectivities are typically not synthetically useful. The discovery of high activity iron and cobalt complexes for alkene hydrogenation suggested that asymmetric variants should be within reach if appropriate chiral ligand architectures could be realized.…”
Section: Stereoselective Alkene Hydrogenation With Pyridine(diimine) ...mentioning
confidence: 99%
“…Thus, base metal catalysts that expand the range of substrates that can be hydrogenated with synthetically useful enantioselectivity would be valuable. While selected examples of asymmetric alkene hydrogenation are known, H 2 is often not the stoichiometric reductant and the yields and selectivities are typically not synthetically useful. The discovery of high activity iron and cobalt complexes for alkene hydrogenation suggested that asymmetric variants should be within reach if appropriate chiral ligand architectures could be realized.…”
Section: Stereoselective Alkene Hydrogenation With Pyridine(diimine) ...mentioning
confidence: 99%
“…Cobalt-containing complexes have been reported as effective catalysts for homogeneous hydrogenation. Studies by Pregaglia, 4 Ohgo, 5 Pfaltz, 6 Corma, 7 Shainyan, 8 Budzelaar, 9 Chirik, 10 Hanson, 11 and Peters 12 were reported to support the potential of ligand-assisted cobalt complex for the catalytic hydrogenation of olefinic compounds.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Unlike carbonyl reductions, which are now well demonstrated with a host of base-metal catalysts, , asymmetric alkene hydrogenations that operate with synthetically useful activities and enantioselectivities are much less developed. Cobalt catalysts for the net hydrogenation of alkenes have been known for some time, but substrate scope is limited, selectivities are generally low, and borohydride rather than hydrogen is used as the terminal reductant. Our laboratory has reported C 1 -symmetric bis(imino)pyridine cobalt methyl complexes that are active for the hydrogenation of prochiral styrene derivatives with high enantioselectivity using H 2 as the stoichiometric reductant …”
Section: Introductionmentioning
confidence: 99%